A High-Performance Li-O2/Air Battery System with Dual Redox Mediators in the Hydrophobic Ionic Liquid-Based Gel Polymer Electrolyte - Feng, Ningning; Wang, Chaoqiang; Wang, Jing; Lin, Yang; Yang, Gang (Batteries (Basel), 2023)
Lithium–oxygen (Li-O2) batteries have captured worldwide attention owing to their highest theoretical specific energy density. However, this promising system still suffers from huge discharge/charge overpotentials and poor cycling stability, which are related to the leakage/volatilization of organic liquid electrolytes and the inefficiency of solid catalysts. A mixing ionic liquid-based gel polymer electrolyte (IL-GPE)-based Li-O2 battery, consisting of a 20 mM 2,5-di-tert-butyl-1,4-benzoquinone (DBBQ) 40 mM N-methylphenothiazine (MPT)-containing IL-GPE and a single-walled carbon nanotube cathode, is designed for the first time here. This unique dual redox mediators-based GPE, which contains a polymer matrix immersed with mixed ionic liquid electrolyte, provides a proper ionic conductivity (0.48 mS cm−1) and effective protection for lithium anode. In addition, DBBQ, as the catalyst for an oxygen reduction reaction, can support the growth of discharge products through the solution–phase pathway. Simultaneously, MPT, as the catalyst for an oxygen evolution reaction, can decompose Li2O2 at low charge overpotentials. Hence, the DBBQ-MPT-IL-GPE-based Li-O2 battery can operate for 100 cycles with lower charge/discharge overpotentials. This investigation may offer a promising method to realize high-efficiency Li-O2/air batteries.